Frações proteicas de sementes de Combretum Leprosum mart.: caracterização de atividade lectínica e investigação do potencial antimicrobiano - Brito Júnior, Antônio Oliveira de (Universidade Federal Rural do Semi-Árido, 2021)
The group of microorganisms is mainly represented by bacteria and fungi, some of which may be pathogens; for example, there are bacteria that cause infections in humans and contaminations in food and fungi that cause damage to economically important cultivars used in the production of grains and other foods. The damage varies by species and target and the spread of these pathogens has caused concern due to the emergence of resistance to commercial antibiotics. Therefore, the search for alternative natural products for the control of pathogenic microorganisms is under constant development. Plants are a source of molecular diversity that can be used as antimicrobial products, such as some lectins. The objective of this work was to characterize the lectin activity and investigate the antimicrobial potential of Combretum leprosum, a plant present in the Caatinga biome that has described biological properties. For this, a fine powder of the seeds was obtained by grinding and sieving and subjected to extractions at 20 °C in saline solution (0.15 M NaCl) and phosphate buffered saline (0.01 M PBS in 0.15 M NaCl) overnight. After filtration and refrigerated centrifugation (8000 rpm, 20 min, 4 °C), the supernatants were named crude extract in 0.15 M NaCl (CE) and buffered crude extract (BCE). In order to obtain concentrated protein fractions, the extracts were saturated by adding ammonium sulfate in three percentage ranges (in relation to volume): 0 - 30 %, 30 - 60 % and 60 - 90 %. Two protein fractions were obtained from CE, fraction 0 - 60 % (F1) and fraction 60 - 90 % (F2), and three fractions from BCE, buffered fraction 0 - 30 % (F1T), buffered fraction 30 - 60 % (F2T) and buffered fraction 60 - 90 % (F3T). Subsequently, the fractions were dialyzed against their respective extraction solutions for ammonium sulfate removal, being called dialyzed F1 (F1D), dialyzed F2 (F2D), dialyzed F1T (F1TD), dialyzed F2T (F2TD) and dialyzed F3T (F3TD). The preparations were evaluated for protein quantification by the method described by Lowry et al. (1951), as for the lectin activity by the hemagglutinating activity (HA) assay using glutaraldehyde-treated human AB-type erythrocytes and the specific HA (SHA) was calculated. The dialyzed fractions were submitted to HA inhibition assays with carbohydrates and to the evaluation of the influence of temperature and pH on HA. The F2D preparation was selected for chromatographic processes for purification or lectin interaction characterization. The EB, F1D and F2D preparations were evaluated for antibacterial potential against some pathogenic bacteria (gram-positive and gram-negative) by cell viability assay using rezasurin as an indicator. All preparations were evaluated for antifungal activity against the pathogens Macrophomina phaseolina and Fusarium falciforme by the agar spread method. The data obtained revealed protein content and high HA titers in the preparations, which were not inhibited by simple carbohydrates. The HA of the preparations was thermostable; F2D and F3TD showed residual HA after heating to 100 °C. For the fractions with lower saturation (F1D, F1TD and F2TD), the alkaline medium (pH > 7.0) favored the increase in the HA of the preparations, but in the acidic medium (pH < 7.0) there was a reduction in the HA; for the higher saturation fractions (F2D and F3TD), the neutral medium allowed the maintenance of HA titers. Although the isolation of lectin from C. leprosum seeds has not been confirmed by electrophoretic protein detection in eluted fractions, the chromatographic profiles of F2D revealed the presence of ligand to the chitin polymer and protein fractions separated by Sephadex G-75, both with lectin activity. The EB, F1D and F2D preparations promoted growth inhibitory activity or bactericidal activity in all bacteria evaluated. None of the preparations promoted an efficient growth inhibition of F. falciforme and M. phaseolina. The results obtained in this work are pioneers in characterizing the protein content, lectin activity and antimicrobial activity of preparations obtained from C. leprosum seeds
Keywords: Proteína; Lectina; Combretaceae; Biotecnologia; Antimicrobiano; Protein; Lectin; Combretaceae; Biotechnology; Antimicrobial; CIENCIAS BIOLOGICAS::BIOTECNOLOGIA